THE ROLE OF THEIR SONGS IN LEARNING ENGLISH - Saydaliyeva, Dilfuza (Журнал иностранных языков и лингвистики, 2023)
Our article will talk about the importance of Uzbek and English songs in education and language learning, as well as the importance of music in education. Uzbek music culture has an ancient and rich heritage. It embodies the national spirit, high human qualities, artistic spirituality, the struggle for independence, and the aspirations and aspirations of our people. The role of education in Uzbek music is also immeasurable. Music is also widely studied in the UK. In music, a lot of attention is paid to young people between the ages of 11 and 14. In the UK, students learn musical instruments and consider singing to be very important in education. You will also get several details on how to play important parts of memory and notes and know their contributions. They use different tones and use appropriate musical instruments such as music, melody, rhythm, chords, and structures in different situations. They analyze and compare musical properties.